Navigating the Fiction of Ernest J. Gaines : A Roadmap for Readers - Clark, Keith, 1963- (Book collections on Project MUSE., 2020)
"Louisiana author of the masterworks "The Autobiography of Miss Jane Pittman" (1971) and "A Lesson before Dying" (1993), Ernest J. Gaines has garnered a fair amount of scholarly attention and much popular success. However, book-length studies devoted solely to his fiction are incommensurate with his prodigious output of seven novels and a collection of short stories. In "Navigating the Fiction of Ernest J. Gaines: A Roadmap for Readers," Keith Clark presents a sustained, nuanced, and original exploration of his fiction that is accessible to non-academic readers and enlightening to scholars, the former audience having maintained a steadfast interest in Gaines's work for over a half a century. The book's core concerns include: how southern blacks and whites continue to wrestle with their tortured history; the chronic and traumatic impact of slavery far beyond its end; the unique physical, psychological, and legal challenges facing southern black men; and Gaines's innovative depictions of black southern women beyond their rather monolithic representations in works by previous southern male authors. Clark greatly benefitted by having access to Gaines in the course of writing his book, and he includes an interview with the writer done in 2014. This welcome, comprehensive guide to the corpus of Gaines's fiction will vivify a great writer's works for readers and fans of all levels"--